Management of Technology as a Tool for Building a Sustainable Competitive Advantage in the Age of Circular Economy and Industry 4.0 - Robert BLAZLAK (Communications of International Proceedings, 2021)
Technology management is understood on the one hand as the process of development and commercialization of technology by university and research institutions. On the other hand, as a process of purchasing new machines and absorption of intellectual property rights or knowledge to a company. Then supported by management practice should be a key factor in creating a competitive advantage. Unfortunately, in the light of the research conducted so far by the author of the article, it can be argued that the investments made in the acquisition of innovative technologies, especially by small and micro enterprises, have nothing to do with the strategic, long-term, approach of building a competitive advantage. Especially if such investment should be carried out as a part of regional or national policy of Industry 4.0 and Circular Economy solutions implementation. The aim of the paper is to analyse the process of technology management in small and micro enterprises from Poland based on own research.
Keywords: Industry 4.0; Circular Economy; technology management; competitive advantage.